Recommendations to optimize health in youth runners - Tenforde, A. S.; Roberts, W. O.; Krabak, B. J.; Davis, I. S.; Fredericson, M.; Luke, A. C.; Ackerman, K. E. (Strength and Conditioning Journal, 2020)
Youth running is defined as participation below age 18. Jumping/multidirectional loading sports (soccer, basketball) may optimize bone health. Psychological development requires monitoring to reduce risk of injuries and burnout. Adequate energy availability is essential for health; screening for disordered eating and optimizing nutrition is important. Injuries during growth spurts are best addressed by identifying the physical maturity of the runner and conventional treatment. Appropriate start of competition and competition distance should be individualized rather than using age-based recommendations and requires careful monitoring. Promoting foot strength and reducing landing impacts may lower injury risk.